Problems of Legal Protection of Trademarks on the Internet: A Case Study of Kazakhstan - Kalmyrza, Gaziza; Alayeva, Gulnaz; Jumabayeva, Karlygash; Aralbaeva, Aigerim; Koshkinbayeva, Aliya (Law, State and Telecommunications Review, 2025)
[Purpose] The study aims to assess the existing legal mechanisms for the protection of trademarks on the Internet in Kazakhstan to identify their shortcomings and develop proposals for their improvement. [Methodology/approach/design] The study conducted a comprehensive analysis of the Civil Code of Kazakhstan and Law No. 456-I “On Trademarks, Service Marks, and Appellations of Origin” using the formal legal method, assessed digital threats through a technology audit, and compared international approaches to trademark protection. [Findings] The main results of the study revealed the problems associated with the protection of trademarks in the Internet environment. Significant gaps in national legislation that hinder the effective suppression of online trademark infringement were identified. A comparative analysis of the legal systems of the United States, China, Germany and France showed that the approaches to intellectual property protection in Kazakhstan differ significantly from international standards, making it difficult for right holders to enforce their rights outside the country. The study also showed that existing enforcement mechanisms are often ineffective in the digital environment, where the distribution of content and anonymity of users create additional challenges. Based on these findings, recommendations were made to improve trademark protection in Kazakhstan, emphasizing the development of more adaptive legal instruments for the digital age. [Practical implications] The article highlights gaps in Kazakhstan’s trademark protection and suggests legal reforms and tech innovations to improve enforcement and ensure fair competition. [Originality/value] This paper highlights deficiencies in Kazakhstan’s digital trademark protection and proposes innovative solutions, offering valuable guidance for policymakers and businesses.